Low levels of high-density lipoproteins are associated with acute kidney injury following revascularization for chronic limb ischemia. (July 2013) - Arora, Pradeep; Davari-Farid, Sina; Gannon, Matthew P.; Lohr, James W.; Dosluoglu, Hasan H.; Nader, Nader D.
Abstract Objectives: Perioperative acute kidney injury (AKI) is not uncommon, following revascularization. HDL has been shown to reduce organ injury in animal models. The aim of the study is to examine the association of HDL on AKI in patients undergoing revascularization for chronic limb ischemia. Methods: All patients who underwent revascularization between June 2001 and December 2009 were analyzed. Patients on dialysis and with incomplete data were excluded. Patients were grouped for HDL < or ≥40 mg/dL. Univariate and multivariate analysis were used to identify factors associated with AKI. Results: A total of 684 patients were included. Eighty-two (12.0%) patients developed postoperative AKI (15.7% in low HDL group vs. 6.3% in high HDL group, p < 0.001). The AKI group were more likely to be older (71.5 ± 10.1 vs. 68.0 ± 10.8, p = 0.01), ASA 4 class (26% vs. 14%, p < 0.001), to have albumin <3 g/dL (59% vs. 32%, p < 0.001), low HDL levels (79% vs. 58%, p < 0.001), DM (61% vs. 44%, p = 0.005), CAD (67% vs. 55%, p = 0.003), preoperative chronic kidney disease (CKD) stage III–IV (55% vs.39%, p < 0.001), to present with critical limb ischemia (82% vs. 63%, p = 0.001), and to be on ACEI (67% vs. 51%, p = 0.006). Multivariate logistic regression analysis showed low HDL (Odds Ratio (OR) 1.66 [1.23–2.24]) and serum albumin levels <3 g/dL (OR 1.66 [1.29–2.13], p < 0.001) were independently associated with increased odds for developing AKI. Propensity score analyses showed low HDL was independently associated with increased odds of AKI (OR 2.4 (1.4–4.2)). Conclusions: AKI following revascularization is not uncommon (12.0%), and lower concentrations of HDL and serum albumin are associated with increased odds of postoperative AKI. There was also a trend of higher prevalence of AKI among those with pre-existing CKD.